Exploring the Academic Landscape of Merdeka Belajar in Higher Education: A Bibliometric Analysis - Ilvi Nirma Husni; Riki Mukhaiyar; Hansi Effendi; Refdinal (Jurnal Penelitian Pendidikan IPA, 2025)
The Merdeka Belajar-Kampus Merdeka (MBKM) policy is a strategic initiative of the Indonesian Ministry of Education, Culture, Research and Technology to revolutionize the higher education system through increasing student learning flexibility and freedom. The purpose of this study is to explore the academic landscape related to the MBKM policy through a bibliometric approach to identify research trends, publication patterns, academic collaboration, and dominant themes that appear in the scientific literature. The method used is bibliometric analysis by utilizing Biblioshiny, VOSviewer, and Microsoft Excel software on 210 documents obtained from the Dimensions database with the keywords “independent learning” and “higher education”. The results showed a significant increase in publications since 2020 with an annual growth rate of 92.56%, indicating high academic interest in MBKM. The top ten most cited articles raised issues of MBKM curriculum implementation, institutional adaptation challenges, and technology integration in learning. The analysis also revealed extensive collaboration between authors and institutions, as well as a diversity of keywords such as “flexible curriculum”, “project-based learning”, and “industry cooperation”. The discussion in this study highlights that while MBKM offers great potential in enhancing student skills, challenges such as faculty readiness, digital infrastructure, and institutional support still need to be addressed. Therefore, the results of this study provide important insights for higher education policy makers in designing more effective and sustainable MBKM implementation strategies.